Some aspects of changing mathematics curricula at school: an interpretative approach to teaching and learning - Saulius Zybartas (Lietuvos Matematikos Rinkinys)
This paper will focus on analysis of changing of educational policy of mathematics education at school. The way of changing (from reproductive approach to interpretative one) and the theoretical foundations (constructivist approach: ontological, epistemological, methodological principles; pedagogical and psychological provisions) are presented in the paper.